The dynamics of the primary school pupils’ linguocultural competence - Цзінь, Лулу (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2019)
This article presents the dynamics of the primary school pupils’ linguocultural competence developed by means of Chinese artistic works. The complex hierarchical structure of the pupils’ linguocultural competence was unified, since it served as the standard for assessing the effectiveness of the teaching process aimed at developing the designated competence within the experimental education at secondary schools. The criterial apparatus for assessing pupils’ learning outcomes is specified. The control exercises and tasks / assignments used as components of the experimental methodology facilitating the formation of the primary school pupils’ linguocultural competence in the framework of learning Chinese are described. The difficulties of mastering the Chinese language are indicated. The author substantiates the dynamics of the developed competence according to specific criteria, taking into account the Ukrainian-Chinese relations, in accordance with: 1) educative and accumulative (indicators: philosophical and fundamental, Confucianism-centric) artistic and authentic (with indicators: ethnically patriotic, epic-folkloric and prose-lyrical); contrastive-comparative (with indicators: general cultural and cultural-specific); operational-interactive (with indicators: culture- and resource-centred, perceptual-cognitive, productive and demonstrative) competencies. Identifying changes in the transformation of the above criteria contents in the context of developing sets of exercises and tasks / assignments for a specific training / education level as well as reviewing the content of the relevant exercises and tasks at each stage of education (primary, secondary, high school) are considered to be the prospects for further research.